2019
DOI: 10.1002/ijc.32532
|View full text |Cite
|
Sign up to set email alerts
|

A low DNA methylation epigenotype in lung squamous cell carcinoma and its association with idiopathic pulmonary fibrosis and poorer prognosis

Abstract: Patients with idiopathic pulmonary fibrosis (IPF) have higher risk of developing lung cancer, for example, squamous cell carcinoma (SCC), and show poor prognosis, while the molecular basis has not been fully investigated. Here we conducted DNA methylome analysis of lung SCC using 20 SCC samples with/without IPF, and noncancerous lung tissue samples from smokers/nonsmokers, using Infinium HumanMethylation 450K array. SCC was clustered into low‐ and high‐methylation epigenotypes by hierarchical clustering analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Similarly, HOXA2 was found to exhibit distinct methylation profiles in at least four cancer sites: lung, colon/rectum, nasopharynx and bile duct [32,55,62,70,71]. In lung squamous cell carcinoma (SCC), HOXA2 was included in a panel of hypermethylated genes that might be useful to stratify SCC into molecular subtypes with distinct prognoses [70].…”
Section: Hoxa Genes Methylated In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, HOXA2 was found to exhibit distinct methylation profiles in at least four cancer sites: lung, colon/rectum, nasopharynx and bile duct [32,55,62,70,71]. In lung squamous cell carcinoma (SCC), HOXA2 was included in a panel of hypermethylated genes that might be useful to stratify SCC into molecular subtypes with distinct prognoses [70].…”
Section: Hoxa Genes Methylated In Cancermentioning
confidence: 99%
“…Similarly, HOXA2 was found to exhibit distinct methylation profiles in at least four cancer sites: lung, colon/rectum, nasopharynx and bile duct [ 32 , 55 , 62 , 70 , 71 ]. In lung squamous cell carcinoma (SCC), HOXA2 was included in a panel of hypermethylated genes that might be useful to stratify SCC into molecular subtypes with distinct prognoses [ 70 ]. It has been suggested that the HOXA2 methylation status, together with the methylation profile of other HOXA genes, may have prognostic value in laryngeal squamous cell carcinoma [ 105 ].…”
Section: Hox Genes Methylation In Cancermentioning
confidence: 99%
“…Low expression of ALDH7A1 in tumors of surgically treated patients with NScLc is associated with a decreased incidence of tumor recurrence, indicating that decreased expression of this gene may predict a good prognosis for these patients (33). Patients with LScc with idiopathic pulmonary fibrosis indicate a significantly decreased methylation level of ALDH7A1 compared with those without fibrosis (34). This observation suggests that methylation status of ALDH7A1 may affect other clinical factors.…”
Section: Discussionmentioning
confidence: 93%
“…In the study, we downloaded three gene expression pro les (GSE53845 [1], GSE92592 [2], and GSE124685 [3]) and two gene methylation pro les (GSE107226 and GSE121849 [4]) from Gene Expression Omnibus (GEO) database (https://www.ncbi.nlm.nih.gov/geo/).…”
Section: Microarray Datamentioning
confidence: 99%
“…For example, Atsushi Hata et al used methylation microarray sequencing to explore the methylation pro les of normal and brotic lung tissue. They found that the low-methylation subgroup signi cantly correlated with IPF [4]. However, so far there has not been any studies to analyze methylation patterns in pulmonary brosis on the gene expression pro le.…”
Section: Introductionmentioning
confidence: 99%